Measurement of returns to scale using non-radial DEA models - Vladimir E. Krivonozhko; Finn R. Førsund; Andrey V. Lychev (University of Oslo, Department of Economics, 2012)
There are some specific features of the non-radial DEA (data envelopment analysis) models which cause some problems under the returns to scale measurement. In the scientific literature on DEA, some methods were suggested to deal with the returns to scale measurement in the non-radial DEA models. These methods are based on using Strong Complementary Slackness Conditions in the optimization theory. However, our investigation and computational experiments show that such methods increase computational complexity significantly and may generate strange results. In this paper, we propose and substantiate a direct method for the returns to scale measurement in the non-radial DEA models. Our computational experiments documented that the proposed method works reliably and efficiently on the real-life data sets.
Keywords: C44; C61; C67; D24; 330; Data envelopment analysis; Returns to scale; Non-radial models; Efficiency; Strong Complementary Slackness Conditions; Data-Envelopment-Analyse